Child care in black and white : working parents and the history of orphanages - Ramey, Jessie B. (Working class in American history., 2012)
This innovative study examines the development of institutional childcare from 1878 to 1929, based on a comparison of two 'sister' orphanages in Pittsburgh: the all-white United Presbyterian Orphan's Home and the all-black Home for Colored Children.